Effect of Graphene Content on Structure and Glossiness of PU/CuCoating Sprayed on Photovoltaic Panel Surface - JIN Hui-ling, DING Lan-hua, CHEN Ji-hong (Cailiao Baohu)
In order to improve the surface energy absorption performance of photovoltaic panels, the graphene-modified PU/Cu coating was sprayed on the surface of photovoltaic panel. The influence of graphene content on the structure and glossiness of coating was analyzed by SEM observation and gloss, emissivity and mechanical properties test. Results showed that the Cu powder was evenly distributed in the coating, and most of which was parallel to the coating surface. The formation of a uniform directional array helped the coating reflect infrared light more efficiently and achieve low emissivity. When the proportion of graphene in the coating increased, a larger surface roughness was formed, which enabled the coating to absorb and scatter visible light more effectively and achieve lower glossiness. The coating with coarser surface structure was obtained by adding graphene, which could effectively control the glossiness of the coating under the condition of maintaining low emissivity, and it could absorb visible light more efficiently after adding black graphene into the coating. The PU/Cu coating modified with graphene could achieve more efficient absorption and scattering of visible light, and obtain lower glossiness while maintaining the original emissivity of the coating. When the content of graphene in the coating increased, the adhesion strength, surface hardness and impact resistance did not change significantly, indicating that the graphene modified PU/Cu coating could maintain stable mechanical strength.